A N A L I S I S K R I T I S A T A S RERUM NOVARUM (1891) DAN OCTOGESIMA ADVENIENS (1971) DARI PERSPEKTIF PEREMPUAN - Tarpin, Laurentius (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2008)
After comparatively analizing Rerum Novarum and Octogesima Adveniens, this paper examines how the historical context of the documents has influenced the Catholic Church's stance on the role of women in public life. Leo XIII, in his encyclical Rerum Novarum, despite his denouncement of inhuman situations of the working class under capitalistic system, gave little attention to the unjust and inhuman situations endured by women. He still held the view that women are primarily destined to do domestic works and not to involve themselves in public areas. Paul VI in his Octogesima Adveniens gave better role to women in society. He promoted the principle of equal opportunities among men and women in social, economic, politic and cultural activities. The research shows that the sensibility of the Catholic Church  towards the real problems of injustice does grow along with the sign of the Times and with the changes of contexts.